Influential Cosmetic Packaging Attributes Toward Customer Purchase Intention - Hasibuan, Maurel Sara; Nuraeni, Shimaditya (Integrasi Sains Media, 2023)
The global skincare industry is experiencing rapid growth, with Indonesia's skincare market expected to be the fastest-growing in the Asia-Pacific region, mainly contributed by the middle-class population. This phenomenon leads to a highly saturated market, requiring brands to differentiate themselves through packaging, increasing companies' investment in packaging. Generational preferences influence packaging design, as Generation Z favors simple and sustainable packaging. This study aims to identify the cosmetic packaging attributes significantly impacting Generation Z's purchase intention. This research identifies visual packaging attributes such as packaging material, closure types, shape, color tone, and graphics as significant factors in customer purchase intention. The study uses a quantitative approach where a questionnaire is distributed to Generation Z residing in Jabodetabek and Bandung. Regression and conjoint analyses are employed to analyze the influence of the independent variable. The regression results indicate that packaging material, shape, and color tone significantly impact customer purchase intention. Conjoint analysis reveals that packaging material is the most important variable, followed by packaging shape, closure, and color tone. The most preferred packaging profile combination comprises glass material, dispensing closure, bottle shape, and tertiary Color. Even though both method results provide different rank significance results, the conjoint analysis provides more relevant results as it depicts packaging as a whole similar to real situations. The findings of this study can be utilized to determine which important packaging attributes need to be focused on during the designing process.